2023
DOI: 10.1055/a-2106-8164
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Training Programs Applied to Young Soccer Players: Effects on Speed-Power Abilities

Tomás T. Freitas,
Lucas A. Pereira,
Pedro E. Alcaraz
et al.

Abstract: We compared the effects of two 4-week strength-power-speed training protocols on physical performance of young soccer players. Twenty-three highly-trained under-20 soccer players were randomly allocated to two mixed-training groups: 1) “traditional” (TRAD: n=11), comprising vertically-oriented strength-power exercises and linear sprints; or 2) “multidirectional” (MULTI: n=12), combining vertically- and horizontally-oriented strength-power exercises, linear sprints, and change-of-direction (COD) drills. Squat j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Tomas T. Freitas and others. [34] achieved positive changes in speed-strength readiness for two different training programs. In the studies of Pasko V. et al [13], the rational structure and content of the speed-strength training of rugby players in the preparatory period was substantiated and developed.…”
Section: Discussionmentioning
confidence: 92%
“…Tomas T. Freitas and others. [34] achieved positive changes in speed-strength readiness for two different training programs. In the studies of Pasko V. et al [13], the rational structure and content of the speed-strength training of rugby players in the preparatory period was substantiated and developed.…”
Section: Discussionmentioning
confidence: 92%
“…However, the combination of squats and hip thrust exercises performed at their respective optimum power zones (i.e., utilizing loads that maximize power output) was superior in enhancing 30-m linear sprint and COD abilities ( Ribeiro et al, 2019 ). Finally, in a recent study, Freitas et al (2023) demonstrated that a multi-training protocol, incorporating vertical and horizontal strength-power exercises (including the hip thrust), was superior to a traditional vertical training protocol (e.g. squats = drop jumps) in improving zigzag velocity among highly-trained under-20 soccer players during a short soccer pre-season.…”
Section: Hip Thrustmentioning
confidence: 99%
“…As emphasized, this exercise appears to be more effective and yields superior results when combined with different types or forms of exercises (e.g., squats, jump squats, plyometrics, etc.) ( Abade et al, 2021 ; Freitas et al, 2023 ; Ribeiro et al, 2019 ). When used within these guidelines, this practical exercise can serve as a suitable and effective stimulus for inducing positive adaptations in sprint performance.…”
Section: Hip Thrustmentioning
confidence: 99%